FolheaRR: um córpus compartilhado de textos jornalísticos roraimenses - Gonçalves, Lana Camila Santos (Universidade Federal de São Carlos, 2024)
This study is based on concepts from Variationist Sociolinguistics (Labov, 2008 [1972]), notions about the correlation between variation and textual-discursive genres (Biazolli, 2010, 2016, 2018; Vieira, 2019; Biazolli; Berlinck, 2021a), discussions on the plurality of norms in Brazilian Portuguese (Faraco, 2008, 2012; Bagno, 2011), and the importance of journalistic texts for sociolinguistic studies (Biazolli, 2010, 2016; Vieira; Lima, 2019; Lima, 2022). These theoretical notions support the general objective of constructing samples of journalistic texts from Roraima, published in the newspaper Folha de Boa Vista (FBV). Among the specific objectives are: I) organizing and detailing criteria for the construction of target samples; II) contributing to discussions on the educated written modality of Brazilian Portuguese, aiming at the initial characterization of educated written Portuguese from Roraima; and III) contributing to the advancement of sociolinguistic studies, including Roraima studies in the analyses of Brazilian Portuguese. FBV is the main communication vehicle of Roraima, and due to the lack of studies describing Roraima Portuguese, the sociocultural and scientific relevance of using this material as a source of language data extraction is emphasized. The constitution of the samples – which, together, form the corpus called FolheaRR –, has five textual-discursive genres: article, chronicle, news, report, and opinion comment. For the constitution of the corpus, this study follows specific guidelines determined by this research and methodological guidelines already established in a larger project, conducted at the national level. After the constitution of the corpus, this work carried out the systematization of independent variables associated with each textual-discursive genre and, based on this, proposed a sociolinguistic analysis suggestion focusing on the lexicon – so that other researchers are encouraged to research linguistic uses at this level, or at other levels of the language, in the present corpus. Thus, through the development of the material and the sociolinguistic factors involved, the potential of FolheaRR for the sociolinguistic study scenario in Roraima became evident.
FolheaRR: a shared corpus of journalistic texts from Roraima
Keywords: Gêneros textuais-discursivos jornalísticos; Córpus linguístico; Folha de Boa Vista; Português de Roraima; Journalistic textual-discursive genres; Linguistic corpus; Folha de Boa Vista; Roraima portuguese; Normas linguísticas; Linguistic norms; LINGUISTICA, LETRAS E ARTES::LINGUISTICA